The Influence of Taste Sensitivity on Fruit and Vegetable Intake among Young Adult Subjects - Aris, Norliyana; Azizan, Aizul Azri; Bahauddin, Ahmad Riduan; Huah, Chai Ming; Houi, Yasmin Ooi Beng (Indonesian Food Science and Technology Journal, 2025)
Abstract— Individual food preferences are crucial predictors of food intake and can be highly influenced by taste sensitivity and perception. It is well known that fruit and vegetables have a variety of tastes and are not only dominated by bitterness. This study aimed to investigate the relationship between taste sensitivity and fruit and vegetable intake. Sensitivity for three basic tastes (e.g sweet, sour, and bitter) was measured using the staircase method whereby individual's sensitivity to the bitter compound 6-n-propylthiouracil (PROP) known as PROP taster status was determined by PROP disc determination. Food frequency questionnaire (FFQ) was used to record the fruit and vegetable intake of subjects. All data were analysed either using one way ANOVA or Pearson correlation at 0.05 confidence level. A total of 80 respondents were involved in this study and it was discovered that among them, 2.5% were PROP nontasters (n=2), 42.5% were medium tasters (n=34), and 55.0% were supertasters (n=44). PROP supertasters were found to have higher sensitivity on bitterness, whereby supertasters had higher bitter intensity ratings (p<0.05) compared to nontasters and medium tasters. In terms of fruit and vegetable intake, the highest consumed fruit was banana while the highest consumed vegetable was onion. Except for onion (p=0.044), no significant difference (p>0.05) was obtained between PROP taster groups and fruit and vegetable intake. Pearson correlation indicated that sweet sensitivity was positively correlated with durian intake (r=0.305) whereas bitter sensitivity was positively correlated to the intake of long bean (r=0.221). No significant relationship was present between sour taste sensitivity on the fruit and vegetable intake.